Effect of crystallization temperature and holding time on flexural strength, color and translucency of nano lithium disilicate glass ceramic - Nouran Gamal; Ingy Nouh; Mohamed Eldemellawy; Amr EL-Etreby (BMC Oral Health)
Abstract Background Ceramists often deviate from the standard crystallization temperatures and holding times recommended by manufacturers, but the effects of these variations remain unclear. The aim of this in-vitro study was to evaluate the effect of different crystallization temperatures and holding times on the color reproduction, translucency and biaxial flexural strength (BFS) of novel lithium disilicate glass ceramic (Amber Mill). In addition, microstructural changes resulting from these altered firing conditions were analyzed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). Methods Fifty-six Amber Mill ceramic discs (n = 56) of 12 mm diameter and 1 mm thickness in shade A2 were prepared and divided into two main groups according to the final crystallization temperature (n = 28); Group (CT1): the manufacturer recommended crystallization temperature 825 °C and Group (CT2): the suggested crystallization temperature 800 °C. Each group was further subdivided into four subgroups according to the holding time (n = 7); subgroup (H1): 15 min (as recommended by the manufacturer) and other suggested holding times, subgroup (H2): 20 min, subgroup (H3): 25 min and subgroup (H4): 30 min. Color reproduction and translucency were measured using a spectrophotometer. Color differences (ΔE00) and relative translucency parameter (RTP) values were calculated. BFS was measured using Piston-on-three ball test. Crystalline structure and microstructural features present in the material were described using XRD and SEM. Two-way ANOVA followed by Tukey’s post hoc test at significance level of p < 0.05 was perfomed. Results Decreasing crystallization temperature decreased color change and decreased translucency of Amber Mill with no influence on flexural strength. Increasing holding time led to decrease in color change with no effect on translucency and flexural strength of Amber Mill. Conclusions The Crystallization temperature suggested in this study showed superior results in terms of color change when compared to the manufacturer’s recommendations, with reduced translucency and no significant impact on the flexural strength of Amber Mill. Suggested holding times decreased color change without affecting either translucency or flexural strength of Amber Mill.